The Dynamic culture of contemporary Korea - Kim, Dong-ok; Cho, Jung-im; Jeong, Hye-won (Korean arts & lifestyle, 2005)
Provides an overview of contemporary popular culture in South Korea. Describes how elements of traditional Korean culture, such as Buddhism, have influenced modern culture. Examines how some traditions have evolved into new forms, such as the development of nanta, a form of performance art that is rooted in traditional samulnori percussion music. Looks at the increasing international interest in Korean movies, pop music, and TV dramas, such as the historical drama Daejanggeum.